Assessing the Effectiveness of Targeted Social Media and Printed Posters as Tools to Recruit Pregnant Women to a Nutrition Trial in Vancouver, Canada. (29th May 2020) - Cochrane, Kelsey; Karakochuk, Crystal; Mayer, Chantal; Devlin, Angela; Elango, Rajavel; Hutcheon, Jennifer
Abstract: Objectives: To assess the effectiveness of targeted advertising on two social media platforms (Facebook and Instagram) compared to printed posters as tools to recruit pregnant women to a clinical trial. Methods: Between September 2019 and January 2020 (16 weeks), 200 posters were distributed and three 10-day online campaigns were run. Online campaigns were targeted to reach pregnant women 19–42 years in Vancouver, Canada. A total of 225 was spent on online ads and 170 on printing posters. Outcomes described for each recruitment strategy include total reach (individuals who saw the ad), total inquiries and resulting enrollments. The odds of enrollment after inquiring from each strategy was evaluated with an odds ratio (OR) and 95% confidence interval (CI). Enrollments per week were calculated by dividing enrollments per group by the time frame of each strategy. Cost per enrollment was calculated by dividing enrollments in each group by their total cost. Results: A total of 104 respondents inquired about participation, of whom 22.1% ( n = 23) enrolled. Social media campaigns reached 7162 women. Of women reached, 1.2% ( n = 84) inquired; 13% ( n = 11) of those who inquired enrolled (∼2.5 enrollments/week). The total reach of the posters is unknown, but 16 women inquired after seeing the poster and 56% ( n = 9) of these women enrolled (∼0.5 enrollments/week). The remaining 3 enrollments were via word of mouth. The odds of enrollment after seeing a poster was 8.5 times higher than after seeing an online ad (OR = 8.5, 95% CI 2.24–32.4). We speculate that this was because women who took down information from a poster and later inquired were more serious about enrolling than those who could immediately respond to an online ad via an e-mail link. However, online ads were more efficient than distribution of posters, requiring less manual labour and resulting in more enrollments per week. Cost per enrollment was similar between groups (∼20 for online ads and ∼19 for posters). Conclusions: Online advertising was more efficient and led to higher total enrollment as compared to poster recruitment, despite the fact that women were less likely to enroll after seeing an online ad as compared to a poster. Costs were relatively similar for use of both tools. Funding Sources: Healthy Starts Catalyst Grant (BC Children's Hospital Research Institute, Vancouver, Canada).